DAMPAK PANDEMI COVID-19 TERHADAP TINGKAT KESEJAHTERAAN PEMBUDIDAYA IKAN KONSUMSI AIR TAWAR - Meilinia, Rista; Bidayani, Endang; Robin (Program Studi Budidaya Perairan Universitas Mataram, 2022)
The existence of the COVID-19 pandemic has become a scourge for the community and several Indonesian sectors, including the fisheries sector. The rapid spread of COVID-19 prompted the government to issue regulations requiring people to carry out large-scale social restrictions. This policy causes community activities and aquaculture production to decrease, consumption of freshwater fish. This study aims to analyze the impact of the COVID-19 pandemic on the welfare level of freshwater fish cultivators in Toboali District, and examine the efforts made by freshwater fish cultivators in Toboali District to maintain their business during the COVID-19 pandemic. This study uses a survey method conducted on several freshwater fish cultivators in Toboali District with the criteria that the cultivators have been cultivating freshwater fish for 2 years and only do the enlargement. The data were analyzed using a descriptive approach. Based on the results of research that the Covid-19 pandemic has an impact on decreasing household income, increasing household spending, and decreasing the quality of education for household members. The declining income of farmers was due to the closed culinary business and the low selling price of fish. The household expenditure of fish cultivators consuming freshwater in a month during the COVID-19 pandemic increased because farmers had to pay bank loan installments. The declining quality of education occurs due to several factors from online learning and children who help work. Various efforts made by freshwater fish cultivators to maintain their business during the COVID-19 pandemic are family members coming to work, reducing the amount of production, reducing household expenses, looking for alternative jobs, utilizing social networks, using social media as a marketing medium, making bank loans. , and maintain fish quality.